Trends and Themes in Accounting Information Systems and Performance: A Bibliometric Study (2021–2025) - Subedi, Purushottam (International Journal of Atharva, 2025)
Accounting Information Systems (AIS) are becoming more important for how organizations improve performance, make decisions, and ensure good governance. Many studies have been done in this area, but the research is scattered across different regions and contexts. A bibliometric study helps to bring these works together, showing the trends, main contributors, and key themes in the field. This study collected articles from the Dimensions AI database between 2021 and 2025. After screening, 212 research papers were analyzed using bibliometric tools. The number of publications has been growing, with a peak in 2024, although newer papers have fewer citations since they are still recent. A few journals, such as JASA and the European Journal of Business and Management Research, dominate the field. Influential works by Monteiro, Khalid, and Sunarta shaped the direction of research. Countries like Indonesia, Jordan, Poland, and Portugal have been leading contributors, while organizations such as Porto Accounting and Business School, Universidade da Madeira, and WSB University have played central roles. Common themes include performance, management, technology, and governance. Thematic analysis further showed five main streams: governance and performance, management systems, information quality, crisis management, and decision-making. Research on AIS and performance is growing fast but remains concentrated in certain journals, countries, and institutions. Earlier studies have gained global attention, while newer ones focus more on digital transformation and practical applications.